Spiritual Journeys and Community Dynamics: Pilgrimage, Religious Tourism, and the Pursuit of Ma‘rifah in Contemporary Indonesia - Zita Malikal Mulki; Kusroni, Kusroni (Faculty of Ushuluddin and Philosophy, 2024)
Religious tourism is a form of travel that focuses on spiritual goals, one of which is through the tradition of pilgrimage to the tombs of saints, such as Sunan Maulana Malik Ibrahim in Gresik, East Jawa, Indonesia. This study aims to explore the relationship between pilgrimage practices, individual spirituality, and its impact on the local community. The research employs a descriptive qualitative method with a literature review approach and limited interviews with members of the Al Khidmah dhikr group in Gresik. The findings reveal that pilgrimage not only fulfills individual spiritual needs but also serves as a means to strengthen moral, social, and economic values within the surrounding community. Additionally, reciting dhikr and manāqib activities have emerged as alternatives for spiritual strengthening during the pandemic, given the restrictions on access to sacred sites. From the perspective of Abū Ḥāmid al-Ghazālī, achieving true spirituality requires a foundation of faith, social etiquette, ritual worship, and purification of the heart through mujāhadah and istiqāmah. Thus, pilgrimage is understood not merely as a physical journey but as an inner journey toward maʿrifah. These findings emphasize that religious tourism plays a significant role in fostering harmony between the spiritual and social dimensions of society.